Natural History Notes. Lanthanotus borneensis (Bornean Earless Monitor). Diet and attempted predation - Veronica, Leah; Pui, Yong Min; Indraneil, Das (Society for the Study of Amphibians and Reptiles, 2023)
Lanthanotus borneensis is a semi-aquatic lizard endemic to Borneo, and except for an earthworm and crustacean found in the gut of one specimen (Losos and Greene 1988. Biol. J. Linn. Soc. 35:379–407) little is known of its diet in the wild. Captive lizards have been reported to eat fish (Harrisson 1961. Sarawak Mus. J. 10:286–292; Mertens 1966. Sarawak Mus. J. 14:320–322), squid, earthworms (Mendyk et al. 2015. Biawak 9:44–49), and frogs (Arroyyan et al. 2021. Treubia 48:103–116). Langer (2017. Russian J. Herpetol. 4:1–10) reported crab remains in the proximity of a female L. borneensis retreat but suspected these were left by the crab-eating Varanus dumerilii. Here, we report on a new prey item and an instance of attempted predation on crabs observed in L. borneensis.